FRI0606 In Vivo Imaging of Phagocyte Migration in Inflammatory Processes by Fluorescent Cell Tracking. (9th June 2015) - Gran, S.; Schäfers, M.; Roth, J.; Vogl, T.
Abstract : Background: Activation, recruitment and migration of phagocytes into infected or inflamed tissue are the very first and crucial events occurring in the onset of an inflammation. The most abundant calcium-binding proteins in phagocytes that are involved in cytoskeletal-membrane interactions during adherence and migration are complexes of S100A8/S100A9. Expression of these proteins, however, shows also a close correlation to disease activity in inflammatory disorders - amongst a broad range of acute as well as chronic disorders especially in rheumatoid arthritis. Objectives: The aim of this study was to analyze S100A8/A9 affected pathways involved in phagocyte migration under inflammatory conditions in vivo by optical imaging of fluorescently labeled cells. Methods: Immortalized murine myeloid progenitor ER-HoxB8 cells obtained from wildtype as well as S100A8/S100A9 -/- mice were differentiated to neutrophils or monocytes/macrophages 1 . Cells were labeled with the membrane-selective fluorescent dyes DIR, DID and VivoTrack680 (IVT), respectively 2 . We analyzed viability and functionality of stained cells in vitro and investigated their ability to migrate to sites of inflammation in vivo in a dermatitis mouse model via fluorescence reflectance imaging (FRI). Results: ER-HoxB8 cells could be effectively stained with all three fluorescent dyes. Labeling of monocytes/ macrophages or neutrophils with DIR, DID or VivoTrack680 did not affect viability or cellular functions like adhesion, migration, phagocytosis or ROS production in vitro . Furthermore, FRI allowed the visualization of migrated phagocytes in a toxic contact dermatitis mouse model in vivo . Both, cells of monocytic and neutrophilic origin - with neutrophils revealing faster migration kinetics - each could be detected at sites of inflammation with high sensitivity. Differential cell labeling allowed direct quantitative comparison of differences in recruitment of wildtype and S100A8/S100A9 -/- neutrophils and monocytes in vivo . Conclusions: Specific and distinguishable labeling of diverse cell types obtained from different mouse lines allows non-invasive tracking and subsequent quantification of migrated cells within the same animal in vivo . Further steps will now focus on analysis and quantification of cellular recruitment – particularly S100A8/S100A9 affected cell migration – during arthritis/in an arthritis mouse model. References: Wang, G. G. et al. Quantitative production of macrophages or neutrophils ex vivo using conditional Hoxb8. Nat. Methods 3, 287–293 (2006). Eisenblätter, M. et al. In vivo optical imaging of cellular inflammatory response in granuloma formation using fluorescence-labeled macrophages. J. Nucl. Med. 50, 1676–1682 (2009). Disclosure of Interest: None declared